C1Q Nephropathy, An Unusual Occurrence in a Middle-Aged South Asian Woman (Medical Forum Monthly, 2024)
We present an interesting but rare occurrence of C1q nephropathy in a middle-aged South Asian woman with a history of edema and fatigue who responded well to steroids. C1q nephropathy is a glomerulopathy characterized by large amounts of C1q deposits in mesangium and is a diagnosis of exclusion after ruling out SLE, affecting a predominately pediatric population. Our case highlights the importance of lateral thinking while dealing with management and treatment outcomes in C1q nephropathy.